Longitudinal Follow-up of Impedance Drift in Deep Brain Stimulation Cases. (26th March 2018) - Wong, Joshua; Gunduz, Aysegul; Shute, Jonathan; Eisinger, Robert; Cernera, Stephanie; Ho, Kwo Wei David; Martinez-Ramirez, Daniel; Almeida, Leonardo; Wilson, Christina A.; Okun, Michael S.; Hess, Christopher W.
Background: Impedance is an integral property of neuromodulation devices that determines the current delivered to brain tissue. Long-term variability in therapeutic impedance following deep brain stimulation (DBS) has not been extensively investigated across different brain targets. The aim was to evaluate DBS impedance drift and variability over an extended postoperative period across common DBS targets. Methods: Retrospective data from 1, 764 electrode leads were included and drawn from 866 DBS patients enrolled in the University of Florida Institutional Review Board-approved INFORM database and analyzed up to 84 months post implantation. An exploratory analysis was conducted to identify trends in impedances using a Mann–Kendall test of trend. Results: There were 866 patients and 1, 764 leads available for analysis. The majority of subjects had Parkinson's disease (60.7%). The mean age at implantation was 58.7 years old and the mean follow-up time was 36.8 months. There were significant fluctuations in the mean impedance of all electrodes analyzed that largely stabilized by 6 months except for the subthalamic nucleus (STN) target, in which fluctuations persisted throughout the duration of follow-up with a continued downward trend (p < 0.001). Discussion: The drift in impedance observed primarily within the first 6 months is in keeping with prior studies and is likely due to surgical micro-lesioning effects and brain parenchyma remodeling at the electrode–tissue interface, typically at values approximating 1, 000 Ω . The differences in impedance trends over time in the various DBS targets may be due to underlying differences in structure and tissue composition.